Cost‐effectiveness of scaling up a whole‐of‐community intervention: The Romp & Chomp early childhood obesity prevention intervention. Issue 9 (17th March 2022) - Tran, Huong Ngoc Quynh; Killedar, Anagha; Tan, Eng Joo; Moodie, Marj; Hayes, Alison; Swinburn, Boyd; Nichols, Melanie; Brown, Vicki
Summary: Background: Given the high prevalence of early childhood overweight and obesity, more evidence is required to better understand the cost‐effectiveness of community‐wide interventions targeting obesity prevention in children aged 0–5 years. Objectives: To assess the cost‐effectiveness of the Romp & Chomp community‐wide early childhood obesity prevention intervention if delivered across Australia in 2018 from a funder perspective, against a no‐intervention comparator. Methods: Intervention costs were estimated in 2018 Australian dollars. The annual Early Prevention of Obesity in Childhood micro‐simulation model estimated body mass index (BMI) trajectories to age 15 years, based on end of trial data at age 3.5 years. Results from modelled cost‐effectiveness analyses were presented as incremental cost‐effectiveness ratios (ICERs): cost per BMI unit avoided, and cost per quality‐adjusted life year (QALY) gained at age 15 years. Results: All Australian children aged 0–5 years ( n = 1 906 075) would receive the intervention. Total estimated intervention cost and annual cost per participant were AUD178 million and AUD93, respectively, if implemented nationally. The ICERs were AUD1 126 per BMI unit avoided and AUD26 399 per QALY gained (64% probability of being cost‐effective measured against a AUD50 000 per QALY threshold). Conclusions: Romp & Chomp has a fair probability of being cost‐effective if delivered at scale.